(untitled) (Journal of the College of Basic Education, 2024)
The aim of the current research is to identify the social responsibility of female students in the kindergarten department and identify self-differentiation and the correlation between social responsibility and self-differentiation. The researcher used the descriptive correlational approach and the sample consisted of (200) female students from the kindergarten department, a delegation. The researcher prepared a social responsibility scale and adopted the (Shakir) scale. (2024) for self-differentiation, and using appropriate statistical methods, the results showed that female students enjoy social responsibility and self-differentiation, and that there is a correlation between responsibility and self-differentiation.